The Effect Of Online Retailers And Perceived Risk On Repurchase Intention Mediated By Trust - Rasum, Alya Presilia; Abadi, Ferryal (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study focuses on online retail consumers who actively make purchases through the leading e-commerce platform, namely Shopee. This study emphasizes more on consumer experience and psychological factors that influence their purchasing decisions. The purpose of this study is to investigate online retailers, perceived risk, and trust on online retail consumers' repurchase intention, by mediating the role of trust. This study aims to provide a better understanding of the factors that influence consumer repurchase intention in the context of e-commerce, so that it can provide valuable input for business practices in improving their marketing strategies and brand management. The sampling technique used is non-probability sampling that has and uses the online retail shopee. In this study, data was collected from 125 respondents who met the criteria. The results of the analysis show that online retailers on trust and trust on repurchase intention have a significant influence. The implications of this finding are that increasing repurchase intention through planned and consistent branding efforts can be the key to increasing consumer trust and preference.